Peripheral histological clearance of cutaneous BCC and SCC excised using the wet blotting technique. (September 2018) - Khalid-Raja, Mamoona; Mistry, Nina; Anari, Shahram
Abstract: Introduction: Accurate identification of the peripheral margin of cutaneous basal cell and squamous cell carcinomas plays a crucial role in ensuring complete excision of the skin cancer. The recommended margin of excision for cutaneous malignancies varies in the current guidelines. The aim of this study was to assess the success rate of peripheral margin clearance with a 4 mm peripheral margin of excision when the clinical margin of the lesion has been identified using the wet blotting technique. Methods: The peripheral margin of each skin cancer was marked using the wet blotting technique and a 4-mm margin of excision rule was applied to all skin cancers regardless of their type and other clinical features. Data collection was performed from patients who were operated on over a period of 34 months (2011 to 2014). Information gathered included patient demographics, clinical details of the lesion and histopathological data. Results: The total number of patients identified were 456. The case notes were reviewed and eventually 276 patients were included and 180 patients were excluded. The histology report showed 95–97% clearance of the peripheral margin in all BCCs and SCCs regardless of their clinical features and their location. Conclusions: Our study has shown that a standard rule of maintaining a 4 mm margin around all head and neck skin BCCs and SCCs, measured after the visible margin of the lesion had been accurately identified by the wet-blotting technique, can successfully achieve 95–97% peripheral clearance of all lesions, irrespective of the subtype, size and location.